Sustainable assessment in manufacturing company - Yasak, Mohd. Fuad (2015)
Knowledge of sustainability concepts and the application of sustainability assessment in Malaysian industries are rather limited. A practical approach towards understanding sustainability concepts and its advantages is by conducting sustainability assessment. Sustainability assessment should consider the three pillars of sustainability via the environment, economic and social. The objectives of the study were to perform sustainability assessment on a popular power tool by determining its sustainability score and to propose improvement to increase the sustainability score. Sustainability assessment was performed using the Math Lab fuzzy logic toolbox. The sub element for environment were solid waste and global warming, whereas for economic, the sub element were cost, quality, technology and process. Finally for social sub element it was the social performance. Outcomes of this study demonstrate the integration between fuzzy logic and sustainability assessment yield the sustainability score for a popular power tool. Methods for improving the sustainability score of the chosen product were also proposed. Finally, some recommendations for future studies were proposed